The Development of Modern Medicine An Interpretation of the Social and Scientific Factors Involved - Shryock, Richard Harrison (University of Pennsylvania Press, 2017)
The relation of the progress of medical science to the social history of humanity. Starting with the seventeenth century, the author analyzes the defeats as well as the triumphs that medicine has gone through to reach its present usefulness
Description based on online resource; title from PDF title page (publisher's Web site, viewed Apr. 18, 2017)
Keywords: Geschichte 1600-1930; Medizin; Phylogenie; Geschichte